Numerical investigations for flow past two square rods in staggered arrangement through Lattice Boltzmann method - Manzoor, Raheela; Naz, Tehmina; Jalil, Maliha; Perveen, Sajida; Akbar, Rahila; Akhtar, Yasmeen; Panezai, Neelam (Annals of Mathematics and Physics, 2021)
A numerical study for two dimensional (2-D) incompressible flow past over two square rods in staggered arrangement detached with a rectangular control rod is conducted by applying single-relaxation-time lattice Boltzmann method (SRT-LBM). This study is conducted basically to reduce the fluid forces and to suppress the vortex shedding through passive control method under the effect of gap spacing between the rods and Reynolds number. The gap spacing (g = s/D) between the rods is taken as g = 1, 3 and 6 whereas, Reynolds number Re= u∞ D/γ is selected within the range of Re = 80 – 200. First validity of code and effect of computational domain along with effect of uniform inflow velocity is checked by considering upstream, downstream and height of computational domain respectively, at Lu = 7.5d, Ld = 30d and H = 14d. After that the effect of gap spacing and Reynolds number on flow structure mechanism is studied. The acquired results are obtained in terms of vorticity contour visualization, power spectrum analysis of lift coefficients and force statistics. Here, three different types of flow regimes, named as i) Irregular Single Bluff Body (ISBB), ii) Flip Flopping (FF) and iii) Anti Phase Synchronized (APS) flow regimes are observed at different values of gap spacing and Reynolds number. In study of force statistics, the values of mean drag coefficients (Cdmean), root mean square of drag coefficients (Cdrms), root mean square of lift coefficients (Clrms) and strouhal number (St) of two square rods are calculated. The values of mean drag coefficients for rod R1 is greater than that of rod R2. The Cdmean for R2 increases with increment in the values of Reynolds, while as Cdmean for R1 having mixed trend. The maximum value of Cdmean is attained at (g, Re) = (1,80) that is 1.8971 for R1 as compared to R2, where existing flow regime is the Irregular single bluff body (ISBB) flow regime. The largest value of Strouhal number is obtained for R2 at (g, Re) = (6, 150) that is 0.1608 along with Anti phase synchronized (APS) flow regime.